2022
DOI: 10.1021/acsanm.2c02391
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Dynamic Study of Color-Changing in Liquid Colloidal Crystals for Electrophoretic Displays

Abstract: Reflective display devices, especially for electrochromic photonic crystals (ECPCs), are of great interest to researchers due to their convenient control approach, wide color regulation range, fast response, and low power consumption. Herein, liquid colloidal crystals (LCCs) of SiO2 nanospheres were prepared through an evaporation-induced self-assembly method and used as a reflective unit for fabricating dynamic ECPC devices. The ECPC device exhibited brilliant controllable structural color across the visible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Tunable photonic crystals stand out for their potential to display continuous colors within individual pixels. Their current implementations, achieving white state reflections between 30% and 60% 151 and reported 20 Hz frequency, 5 could be an interesting venue to explore further. The switching speed needs to be improved to yield video playback possibilities, as well as further reduction of the angle dependence and the ability to show white.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tunable photonic crystals stand out for their potential to display continuous colors within individual pixels. Their current implementations, achieving white state reflections between 30% and 60% 151 and reported 20 Hz frequency, 5 could be an interesting venue to explore further. The switching speed needs to be improved to yield video playback possibilities, as well as further reduction of the angle dependence and the ability to show white.…”
Section: Discussionmentioning
confidence: 99%
“…The line between a static printed medium and a dynamic digital display could become remarkably indistinct. Electrophoretic microcapsule 35 155 44 154 43 157 23 155 15 154 14 157 2.1 156 226 157 0.58 157 Electrophoretic total internal reflection 55 46 83 158 40 48 20 158 16 48 28 46 30 158 212 158 227 48 0.029 48 LCD reflective 9 166 25 166 60 166 69 166 0.03 166 LCD cholesteric 30 159 35 77 10 159 25 77 0.8 77 100 77 4.7 77 Electrowetting 40 168 65 162 55 169 1.7 162 Electrochromic 40 160 47 161 12 160 10 161 1 160 200 171 1.1 161 Tunable photonic crystals 60-30 151 N/A 1 151 0.125 172 20 5 N/A N/A…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[23][24][25] Nevertheless, the color chromaticity still needs to be improved. Researchers found that black substances, including graphene, 26 carbon black (CB), 27,28 and black dispersion dyes, 29 were capable of reducing the incoherent scattered light, further improving reflectivity and color chromaticity. Zhang et al 27 prepared hollow SiO 2 with different CB contents, and the assembled photonic crystal ink showed excellent chromaticity and high crystallinity.…”
Section: Introductionmentioning
confidence: 99%
“…This colloidal crystal that can induce color change is used for various applications. For example, mechanical discoloration induced by strain or pressure is particularly suitable for optical sensing and visual communication, , which helps in development of dynamic environments and clinical or health monitoring assistive devices. Similarly, electrochromic or thermochromic photonic crystals are also used in smart windows, displays, and chiral sensors. By combining the response characteristics of photonic crystals, diverse colloidal photonic crystal patterns can be prepared. Under appropriate conditions, invisible photon patterns can be selectively displayed.…”
mentioning
confidence: 99%